BUDGET POLICY OF FINANCIAL SUPPORT OF UKRAINE’S DEFENSE CAPACITY - Sidelnykova , L.P.; Rudyk S.О. (The actual problems of regional economy development, 2021)
The article is directed at studying the peculiarities of the budget policy of financial support of Ukraine's defense capabilities during 2011-2020. It is proved that due to permanent underfunding, the fighting capacity of the Ukrainian army at the beginning of the Russian aggression was reduced. It is established that the negative trend of insufficient funding for defense measures persists today, not allowing Ukraine to achieve the required level of state protection, so the issues of effective formation and use of state budget expenditures on defense are still relevant. The purpose of the article is to monitor the current realities of financing the defense sector and identify areas for optimizing the financial support of Ukraine's defense capabilities in terms of increasing hybrid challenges. The specifics of the scientific tasks that are the subject of the study required the use of a set of special methods, the use of which helped to identify trends in the financing of defense expenditures and identify real and potential threats and problems of financial support of Ukraine's defense capabilities. The level of meeting the needs of the state to finance national defense is characterized by three areas: defense spending according to the functional classification of expenditures; budget programs of the Ministry of Defense of Ukraine according to program classification; financial support for servicemen according to the economic classification of budget expenditures. As a result of the study, it was proved that a key aspect of Ukraine's budget policy regarding the financial support of its defense capabilities is the effective formation and use of state budget funds to finance the Armed Forces of Ukraine. In the context of intensifying hybrid challenges, the defense budget of our state should gradually grow, providing for the modernization of the Armed Forces of Ukraine through the purchase of weapons and military equipment; the transition of the security and defense sector to NATO standards; building a professional army as a complex process in which the staffing of the Armed Forces under contract is only one of the elements; increasing the level of financial and material security and social protection of servicemen.